JAPANESE ADVERTISEMENT FOR IMPROVING STUDENTS READING ABILITY - Sri Aju Indrowaty (Jurnal Japanedu: Pendidikan dan Pengajaran Bahasa Jepang, 2018)
Advertising is a form of communication that discloses information or messages and promotes the speaker's intent to his or her opponent. The language used in advertising is a language that is easy to understand and persuasive so that the opponent can speak as the speaker means. From advertisements in magazines, used for student learning in Dokkai 5. Dokkai or reading is a very important course for students to welcome the office work normally done by Japanese language graduates. In the office when working related Japanese often read documents and translate documents. In this research, using advertising media because it is usually written in large and striking letters.